Microbiological profile of bronchoalveolar lavage fluid in patients with chronic respiratory diseases: a tertiary care hospital study - KU, Vivek; Kumar DM, Nutan (International Journal of Medical Research and Review, 2016)
Objective: Chronic respiratory diseases account for 4 million deaths annually. Infections are most frequent cause of exacerbations. Bronchoalveolar lavage has improved sensitivity and specificity of diagnostic techniques in diagnosis of pulmonary infections. Hospital antibiograms are an important component of detecting and monitoring trends in antimicrobial resistance. Materials and Methods: Retrospectively BAL fluid reports of patients with chronic respiratory diseases undergoing bronchoscopy in KIMS Hospital were collected under aseptic precautions. Antibiotic and antifungal susceptibility testing was done for bacterial isolates and fungal isolates. Results: Among 100 BAL sample cultured for bacterial etiology, 38 samples showed growth, 56 samples showed no growth. Monomicrobial growth of the BAL culture was seen in 34 cases (89%) and polymicrobial growth was seen in 4 (11%). In the antimicrobial susceptibility testing, 100% sensitivity was noted to linezolid, levofloxacin, tetracycline, vancomycin, netilmycin and tobramycin. Pipercillin-tazobactum and imipenem show sensitivity of 96.2%. Antibiotics showing high resistance pattern were ampicillin (73%) and amoxicillin-clavulanic acid (52.3%). On fungal culture, 27 cases showed growth, of which candida albicans was the most common isolate (37%). Aspergillus accounted for 4 isolates (14.8%), aspergillus niger being predominant. All isolates of candida were 100% susceptible to fluconazole, itraconazole and voriconazole except candida albicans, 10% showed resistance to voriconazole. All isolates of aspergilluis were 100% susceptible to voriconazole and 100% resistance to fluconazole. Conclusion: Bronchoalveolar lavage has improved sensitivity and specificity in diagnosis of pulmonary infections. An updated local antibiogram for each hospital based on local bacteriological patterns and susceptibilities is essential to guide initial empiric therapy.